Seaweed Farmer Income and Family Socioeconomic Life - Ernawati S. K (Pinisi Journal of Social Science, 2023)
Fluctuating incomes of seaweed farmers are considered to affect the socioeconomic life of their families. For this reason, this research article aims to describe the income of seaweed farmers in relation to the socioeconomic life of their families. The research method uses descriptive-qualitative methods. The determination of research informants is carried out deliberately based on research objectives and certain considerations. The sources of research data, are 1) Primary data, which is collected from direct observation and interviews. 2) Secondary data, which is obtained from library sources and data relevant to research. Data analysis techniques are descriptive-qualitative. The results showed that the income of farmers from trying to farm seaweed in Lasitae Village can be said to be sufficient to meet the needs of their families. This is supported by the area of land owned and the success of farmers during each harvest and the selling price of seaweed which is quite good today. This can be seen from the awareness that farmers have to send their children to school even though it requires a large cost. The motivation to send children to school is seen up to graduating from high school and even to the college level.  Most of them already have adequate facilities and facilities to support their daily activities and families.  Also, have a habitable place to live from the income they set aside from the results of farming seaweed.